Factor Structure and Psychometric Properties of the Family Quality of Life Questionnaire for Children With Developmental Disabilities in China - Huang, Rujun; Shen, Renhong; Xu, Su Qiong (Frontiers in Psychology, 2020)
The purpose of this study was to explore the factor structure and psychometric properties of Chinese version of Family Quality of Life Questionnaire(Chinese FQoL-Q) for children with developmental disabilities under the background of Chinese culture. The item analysis, exploratory factor analysis and confirmatory factor analysis and reliability test were carried out on survey data from a sample of 845 family Children with development disabilities. It was found that the Chinese FQoL-Q involves seven factors with 35 items, including economy and leisure, physical and mental health, parenting, family communication, support from others, professional support and career development. The measurement model of Chinese FQoL-Q reflected the traditional Chinese culture and parents’ perception of education or rehabilitation for their children in China. The Chinese FQoL-Q is reliable and valid for assessing the quality of life for family members with development disabilities.